THE IMPACT OF FAMILY PLANNING ON MATERNAL HEALTH IN QUETTA, BALOCHISTAN: A QUALITATIVE STUDY - JAMIL, Z; KHAN, A; BIBI, R (Biological and Clinical Sciences Research Journal, 2024)
Balochistan, a region with one of the highest maternal mortality rates in Pakistan, faces significant challenges in maternal health. This qualitative study focuses on the impact of family planning on maternal health in Quetta, Balochistan, emphasizing the importance of understanding and improving health outcomes for women and their families. Objectives: The primary aim of this study is to explore the experiences and perspectives of women regarding the use of family planning methods and their impact on maternal health and well-being. It aims to compare the health outcomes of women who have utilized family planning methods with those who have not. Method: The research design includes in-depth interviews and focus group discussions (FGDs) with a diverse sample of women aged 18-45 years and healthcare providers at Sandeman Provincial Hospital, commonly known as Civil Hospital, in Quetta. Purposive sampling was employed to account for age, socioeconomic status, and education level variations. Forty-seven in-depth interviews were conducted to gather rich, contextual data. Thematic analysis was used to identify recurring themes and patterns in the responses. Results: Preliminary findings indicate several key themes, including the motivations for choosing family planning methods, the impact of these methods on reducing pregnancy risks, improving spacing between pregnancies, and enhancing postpartum recovery. Additional insights were gained into the factors influencing the adoption of family planning services, such as cultural norms, religious beliefs, and access to healthcare and information. Conclusion: The study underscores the critical role of family planning in enhancing maternal health outcomes in Quetta, Balochistan. It highlights the need for targeted educational and healthcare interventions to improve the accessibility and acceptance of family planning services, thereby contributing to the well-being of women and their families in the region.